Prevalence of Hypocalcemia in Patients with Acute Ischemic Stroke at a Tertiary Care Hospital - Ali Shuaib Ashraf, Ali Hassan, Muhammad Hamza Saeed, Arsalan Shamim, Haleem Hammad, Yasir Salim, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To ascertain the prevalence of hypocalcemia in patients with acute ischemic stroke at a tertiary care hospital and to analyze the mean scores on the modified Rankin Scale, assessing the stroke severity, in patients both with and without hypocalcemia." Study Design: It was a cross sectional study. Setting: Deptt. of Medicine, Services Hospital, Lahore. Methodology: 100 eligible patients were examined the modified Rankin scale at the time of presentation, recording the scores. To ensure accuracy, overnight fasting was observed, and a 5 ml early morning fasting blood sample was collected via venipuncture using aseptic techniques, administered by the researcher. These blood samples were then sent in serum vials to the pathology lab and hypocalcemia was labeled. Results: Mean age ± standard deviation was calculated to be 47.58 ± 8.43 years, 63 participants (63%) were male, while 37 participants (37%) were female. The mean Rankin score was determined as 3.67 ± 1.16. Furthermore, the frequency of hypocalcemia among patients with acute ischemic stroke who presented at the tertiary care hospital was observed in 53 cases (53%). To assess the severity of stroke, a comparison was made between the mean scores on the Modified Rankin Scale for patients with and without hypocalcemia. The results showed a mean score of 4.50 ± 0.67 in the group with hypocalcemia and 2.61 ± 0.69 in the group without hypocalcemia, with a p-value of 0.0001. Conclusion: Acute ischemic stroke patients at a tertiary care hospital often have hypocalcemia. Additionally, patients with hypocalcemia exhibit significantly higher mean scores on the modified Rankin Scale, indicating increased stroke severity compared to those without hypocalcemia. Keywords: Acute ischemic stroke, hypocalcemia, modified Rankin Scale, severity of stroke